REVENUE GUARANTEES IN PUBLIC PRIVATE PARTNERSHIPS - Emek, Uğur (PEOPLE: International Journal of Social Sciences, 2024)
Historically, governments have been responsible for financing, construction and maintenance of infrastructure projects in such sectors as energy, transport, education and health. During last decades, public finance has been inadequate to deliver infrastructure services in terms of construction and renovation. For this reason, the private sector has played an important role to finance greenfield (new) and brownfield (existing) projects in the form of Public Private Partnerships (PPPs). Infrastructure investment includes certain risks such as financing, construction, operation and demand. The private sector can control first three risks better than demand risk. The estimation of future demand risk is uneasy in countries with volatile GDP, inflation, currency or users’ willingness to pay tolls. Further, depending on optimism bias or misrepresentation, planners may overestimate the future demand. Since transport traffics have been lower than projected tolls, the private sector may become reluctant to undertake the toll revenue risk and willing to transfer this risk to the government. Minimum revenue guarantees (MRG) is one method to transfer revenue risk to the government among others. Turkish Government has preferred the MRG in the transport projects. Under MNR scheme, the government reimburses the private partner when actual toll falls short of the projected revenue over operating period. On the other hand, motorway PPP projects are divided to several parts by the Turkish Government. Once the private partner completes one part earlier in the construction period, the Turkish government takes that part into operation and MNR commences for this part. Thus, the private partner acquires extra MNR during the construction period in addition to the operating term. Consequently, front loaded MNR is used as cross-subsidy to finance other parts’ construction cost of the related project.